Family and Friend Perceptions of Quality of End-of-Life Care in Medicare Advantage vs Traditional Medicare - Ankuda, Claire K; Kelley, Amy S; Morrison, R. Sean; Freedman, Vicki A; Teno, Joan M (JAMA Network Open, 2020)
IMPORTANCE: Medicare Advantage (MA) insures an increasing proportion of Medicare beneficiaries, but evidence is lacking on patient or family perceptions of the quality of end-of-life care in MA vs traditional Medicare. OBJECTIVE: To determine if there is a difference in quality of care reported by family and friends of individuals who died while insured by MA vs traditional Medicare at the end of life. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study used the 2011 to 2017 Medicare-linked National Health and Aging Trends Study to conduct population-based survey research representing 8 668 829 Medicare enrollees. Included individuals were 2119 enrollees who died when aged 65 years or older, with quality of care reported by a family member or close friend familiar with the individual’s last month of life. Analysis was conducted in July 2020. EXPOSURES: MA enrollment at the time of death or before hospice enrollment. MAIN OUTCOMES AND MEASURES: Perception of end-of-life care was measured with 9 validated items, with the primary outcome variable being overall care rated not excellent. We conducted a propensity score–weighted multivariable model to examine the association of each item with MA vs traditional Medicare enrollment. The propensity score and multivariable model included covariates capturing demographic and socioeconomic factors, function and health, and relationship of the respondent to the individual who died. The sample was then stratified by hospice enrollment and setting of care in the last month. RESULTS: Of 2119 people in the sample, 670 individuals were enrolled in MA at the time of death or prior to hospice (32.7%) and 1449 were enrolled in traditional Medicare (67.3%). In survey-weighted percentages, 53.6% (95% CI, 51.0% to 56.1%) were women and 43.4% (95% CI, 41.5% to 45.3%) were older than 85 years at the time of death. In the adjusted model, family and friends of individuals in MA were more likely to report that care was not excellent (odds ratio, 1.28; 95% CI, 1.01 to 1.61; P = .04) and that they were not kept informed (odds ratio, 1.48; 95% CI, 1.06 to 2.05; P = .02). For those in nursing homes, there was an estimated probability of 57.2% of respondents reporting that care was not excellent for individuals with traditional Medicare, compared with 77.9% of respondents for individuals with MA (marginal increase for those in MA, 0.21; 95% CI, 0.08 to 0.32; P = .001). CONCLUSIONS AND RELEVANCE: In this cross-sectional study of people who died while enrolled in Medicare, friends and family of those in MA reported lower-quality end-of-life care compared with friends and family of those enrolled in traditional Medicare. These findings suggest that, given the rapid growth of MA, Medicare should take steps to ensure that MA plans are held accountable for quality of care at the end of life.